2018
DOI: 10.1038/s41467-018-04343-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid labelling and covalent inhibition of intracellular native proteins using ligand-directed N-acyl-N-alkyl sulfonamide

Abstract: Selective modification of native proteins in live cells is one of the central challenges in recent chemical biology. As a unique bioorthogonal approach, ligand-directed chemistry recently emerged, but the slow kinetics limits its scope. Here we successfully overcome this obstacle using N-acyl-N-alkyl sulfonamide as a reactive group. Quantitative kinetic analyses reveal that ligand-directed N-acyl-N-alkyl sulfonamide chemistry allows for rapid modification of a lysine residue proximal to the ligand binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(228 citation statements)
references
References 52 publications
8
208
0
Order By: Relevance
“…Hamachi and co-workers have developed a wide range of LDL methods capable of selectively modifying native proteins in a 'traceless' manner, in which the ligand leaves its binding site after the labelling reaction and the protein is able to perform its native function 14 . These methods include exchange/cleavage approaches based on electrophilic phenylsulfonate esters [15][16][17] , acyl imidazoles 18,19 , N-sulfonyl pyridines 20 , or N-acyl-N-alkyl sulfonamides 21 and catalyst tethering approaches based on N,N-dimethylaminopyridine (DMAP) [22][23][24] or oxime reagents 25 . In addition, several groups have developed LDL reagents incorporating transition metal catalysts.…”
mentioning
confidence: 99%
“…Hamachi and co-workers have developed a wide range of LDL methods capable of selectively modifying native proteins in a 'traceless' manner, in which the ligand leaves its binding site after the labelling reaction and the protein is able to perform its native function 14 . These methods include exchange/cleavage approaches based on electrophilic phenylsulfonate esters [15][16][17] , acyl imidazoles 18,19 , N-sulfonyl pyridines 20 , or N-acyl-N-alkyl sulfonamides 21 and catalyst tethering approaches based on N,N-dimethylaminopyridine (DMAP) [22][23][24] or oxime reagents 25 . In addition, several groups have developed LDL reagents incorporating transition metal catalysts.…”
mentioning
confidence: 99%
“…The ligand‐directed tosyl chemistry (Scheme a), ligand‐tethered‐DMAP derived nucleophilic catalysis, and ligand‐directed acyl imidazole (LDAI) capacitate the installation of biophysical probes to the protein (Scheme b) . Hamachi's group also demonstrated that sulfonamide derivatives could direct an electrophile for precise modification of a lysine residue . Sodeoka and co‐workers also developed the affinity labeling of Lys residue with simple chemical probe bearing small molecule o‐nitrobenzoxadiazole unit (o‐NBD, Scheme c) .…”
Section: Single‐site Labeling Of Native Proteinsmentioning
confidence: 99%
“…For this reason, affinity‐guided probes have also been developed for transfer of a biotin handle to the protein. In these cases, the biotin handle was used for blotting of the target protein that had been labeled in living systems …”
Section: Label‐containing Moietymentioning
confidence: 99%
“…Recently, sulfonating probes have been included in the repertoire of affinity‐guided reactive moieties (Figure A) . An N ‐sulfonyl pyridone reactive moiety was used to transfer a sulfonyl functionality to a protein with the probe displaying superior labeling efficiency and kinetics compared to the benzenesulfonates and imidazole carbamates.…”
Section: Reactive Moietymentioning
confidence: 99%
See 1 more Smart Citation